Priority research needs to inform amphibian conservation in the Anthropocene - Campbell Grant, Evan H. (2023)
The problem of global amphibian declines has prompted extensive research over the last three decades. Initially, the focus was on identifying and characterizing the extent of the problem, but more recently efforts have shifted to evidence-based research designed to identify best solutions and to improve conservation outcomes. Despite extensive accumulation of knowledge on amphibian declines, there remain knowledge gaps and disconnects between science and action that hamper our ability to advance conservation efforts. Using input from participants at the ninth World Congress of Herpetology, a U.S. Geological Survey Powell Center symposium, amphibian on-line forums for discussion, the International Union for Conservation of Nature Assisted Reproductive Technologies and Gamete Biobanking group, and respondents to a survey, we developed a list of 25 priority research questions for amphibian conservation at this stage of the Anthropocene. We identified amphibian conservation research priorities while accounting for expected tradeoffs in geographic scope, costs, and the taxonomic breadth of research needs. We aimed to solicit views from individuals rather than organizations while acknowledging inequities in participation. Emerging research priorities (i.e., those under-represented in recently published amphibian conservation literature) were identified, and included the effects of climate change, community-level (rather than single species-level) drivers of declines, methodological improvements for research and monitoring, genomics, and effects of land-use change. Improved inclusion of under-represented members of the amphibian conservation community was also identified as a priority. These research needs represent critical knowledge gaps for amphibian conservation although filling these gaps may not be necessary for many conservation actions.